17ß-Estradiol regulates mTORC2 sensitivity to rapamycin in adaptive cardiac remodeling. - Angelika Kusch; Maria Schmidt; Dennis Gürgen; Daniel Postpieszala; Rusan Catar; Björn Hegner; Merci M Davidson; Shokoufeh Mahmoodzadeh; Duska Dragun (PLoS ONE, 2015)
Adaptive cardiac remodeling is characterized by enhanced signaling of mTORC2 downstream kinase Akt. In females, 17ß-estradiol (E2), as well as Akt contribute essentially to sex-related premenopausal cardioprotection. Pharmacologic mTOR targeting with rapamycin is increasingly used for various clinical indications, yet burdened with clinical heterogeneity in therapy responses. The drug inhibits mTORC1 and less-so mTORC2. In male rodents, rapamycin decreases maladaptive cardiac hypertrophy whereas it leads to detrimental dilative cardiomyopathy in females. We hypothesized that mTOR inhibition could interfere with 17β-estradiol (E2)-mediated sexual dimorphism and adaptive cell growth and tested responses in murine female hearts and cultured female cardiomyocytes. Under physiological in vivo conditions, rapamycin compromised mTORC2 function only in female, but not in male murine hearts. In cultured female cardiomyocytes, rapamycin impaired simultaneously IGF-1 induced activation of both mTOR signaling branches, mTORC1 and mTORC2 only in presence of E2. Use of specific estrogen receptor (ER)α- and ERβ-agonists indicated involvement of both estrogen receptors (ER) in rapamycin effects on mTORC1 and mTORC2. Classical feedback mechanisms common in tumour cells with upregulation of PI3K signaling were not involved. E2 effect on Akt-pS473 downregulation by rapamycin was independent of ERK as shown by sequential mTOR and MEK-inhibition. Furthermore, regulatory mTORC2 complex defining component rictor phosphorylation at Ser1235, known to interfere with Akt-substrate binding to mTORC2, was not altered. Functionally, rapamycin significantly reduced trophic effect of E2 on cell size. In addition, cardiomyocytes with reduced Akt-pS473 under rapamycin treatment displayed decreased SERCA2A mRNA and protein expression suggesting negative functional consequences on cardiomyocyte contractility. Rictor silencing confirmed regulation of SERCA2A expression by mTORC2 in E2-cultured female cardiomyocytes. These data highlight a novel modulatory function of E2 on rapamycin effect on mTORC2 in female cardiomyocytes and regulation of SERCA2A expression by mTORC2. Conceivably, rapamycin abrogates the premenopausal "female advantage".